GE_GERICHTE P/18396/2023 vom 14. März 2024 - GE Cour de justice (2024)
PREUVE;VIDÉOSURVEILLANCE;PROTECTION DES DONNÉES;PRÉSOMPTION D'INNOCENCE;PRODUIT CHIMIQUE;LÉGUME;ILLICÉITÉ | CPP.140; CPP.141; CP.179quater; CPP.269; CPP.10; LPD.4